DNA Replicons for Plant Genome Engineering - Baltes, Nicholas J. (American Society of Plant Biologists, 2014)
Sequence-specific nucleases enable facile editing of higher eukaryotic genomic DNA; however, targeted modification of plant genomes remains challenging due to ineffective methods for delivering reagents for genome engineering to plant cells. Here, we use geminivirus-based replicons for transient expression of sequence-specific nucleases (zinc-finger nucleases, transcription activator–like effector nucleases, and the clustered, regularly interspaced, short palindromic repeat/Cas system) and delivery of DNA repair templates. In tobacco (Nicotiana tabacum), replicons based on the bean yellow dwarf virus enhanced gene targeting frequencies one to two orders of magnitude over conventional Agrobacterium tumefaciens T-DNA. In addition to the nuclease-mediated DNA double-strand breaks, gene targeting was promoted by replication of the repair template and pleiotropic activity of the geminivirus replication initiator proteins. We demonstrate the feasibility of using geminivirus replicons to generate plants with a desired DNA sequence modification. By adopting a general plant transformation method, plantlets with a desired DNA change were regenerated in <6 weeks. These results, in addition to the large host range of geminiviruses, advocate the use of replicons for plant genome engineering.